Native American Urban Narratives: Theodore Van Alst’s Sacred Smokes and Tommy Orange’s There There - Sanja Runtić; Marija Krivokapić ([sic])
The article examines the representation of Native American urban identity in Theodore Van Alst’s Sacred Smokes (2018) and Tommy Orange’s There There (2018). Drawing upon Stuart Hall’s and James Clifford’s theories of identity and diaspora and Robert Young’s distinction between the “organic” and the “diasporizing” modes of hybridity, it analyzes hybrid strategies through which these texts define their characters’ complex diasporic experience and extend the literary tradition of “survivance.” The paper argues that by exploring the concepts of history, community, and home and by emphasizing the narrative, imaginative, and relational aspects of their characters’ traveling identities, Van Alst’s and Orange’s texts remain strongly rooted in Native cultural perspective, in particular the “synecdochic” sense of self and the literary trope of “homing.” It also maintains that these characters’ precarious diasporic situation, albeit confining, allows them the freedom to (re)imagine themselves and thereby transcend their unstable deterritorialized and transcultural position and the realities of dispersal and alienation by inventing new modes of self-coherence and cultural continuity.